Analisis Faktor-Faktor Yang Mempengaruhi Realisasi Pendapatan Asli Daerah Dan Strategi Penggalian Potensinya Di Kabupaten Landak - B61111027, Frans Riduan (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACK The target of this research is: to study and analyze factors which influence the original earnings realization of Landak sub-province area, and to know strategy which have been conducted by Landak sub-province local government in digging the source of PAD utilize to improve original revenue realization of area. Statistical test using SPSS 20.0 series showed an adjusted R2 value of 0.908, which means the effect of independent variables and population growth can contribute to the increase in revenue realization of revenue of 90,8%, while the remaining 9,2% is influenced by other factors, Test simultaneous regression independent variables: growth factors and factors of population has a significant impact on revenue realization of PAD in the Porcupine District. Thus, the alternative hypothesis can be accepted. Variable regression of economic growth and a population of partially variables significant influence on the realization of PAD. Strategy of original earnings of Landak Sub-Province area is through: Intensification, that is return data and rejuvenate tax subject and object and also retribution area., Extensification, that is digging the source of acceptance of new tax, and Diversification, that is improve the public service. Â Key words : Local Original Income,Â economic growth , amount of resident